2019
DOI: 10.1088/1367-2630/ab4f4f
|View full text |Cite
|
Sign up to set email alerts
|

All-acoustic signal modulation and logic operation via defect induced cavity effects in phononic crystal coupled-resonator acoustic waveguides

Abstract: A coupled resonant acoustic waveguide (CRAW) in a phononic crystal (PnC) was engineered to manipulate the propagation of ultrasonic waves within a conventional phononic bandgap for wavelength division multiplexing. The PnC device included two, forked, distinct CRAW waveguide channels that exhibited strong frequency and mode selectivity. Each branch was composed of cavities of differing volumes, with each giving rise to deep and shallow 'impurity' states. These states were utilized to select frequency windows w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…PnBGs represent the frequency ranges of the waves that are not supported within the phononic structure, and thereby their transmission through the crystal is blocked. The PnBGs can be modified by tailoring the impedance contrast among their components, i.e., elastic constants or the mass density of the scatters and matrix, by adjusting the filling fraction ratio or the material parameters (Zhou, 2009;Pennec, 2010) or the spatial distribution of their components (Zhang Z., 2017;Reyes, 2019). Several manufacturing techniques have been used for the design of PnCs with tunable PnBGs through external stimulus directly acting on one or both of their components, making it possible to realize active PnCs whose acoustic properties are sensitive to electric or magnetic fields (Allein, 2016;Ponge, 2016), stress (Zhang P., 2017), or heat absorption (Walker, 2014), among other factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PnBGs represent the frequency ranges of the waves that are not supported within the phononic structure, and thereby their transmission through the crystal is blocked. The PnBGs can be modified by tailoring the impedance contrast among their components, i.e., elastic constants or the mass density of the scatters and matrix, by adjusting the filling fraction ratio or the material parameters (Zhou, 2009;Pennec, 2010) or the spatial distribution of their components (Zhang Z., 2017;Reyes, 2019). Several manufacturing techniques have been used for the design of PnCs with tunable PnBGs through external stimulus directly acting on one or both of their components, making it possible to realize active PnCs whose acoustic properties are sensitive to electric or magnetic fields (Allein, 2016;Ponge, 2016), stress (Zhang P., 2017), or heat absorption (Walker, 2014), among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…The coupling strength can essentially control the Q factor of PnC with defect-based waveguides. The periodicity of separation between each defect can significantly modify the Q factor when the defect is made of a scatterer with different features with respect to the rest of the defects within the PnC (Wang, 2018;Reyes, 2019). Besides, the material and geometrical features of the defect can also influence the Q factor.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results have demonstrated that groups of defects continuously induced in a phononic crystal can function as waveguides for waves whose frequencies fall within their phononic bandgap. [3,5] The experimental transmission spectra for both designed defect-based acoustic interferometers, DM and HM, are depicted in Figure 2a in red and blue lines, respectively, covering the frequency range from 400 to 460 kHz. Acoustic response was experimentally recorded in dBm units, which have its logarithmic equivalence in watt (+20 dBm (0.1 W)), and represent power quantity.…”
Section: Ultrasonic Spectroscopy Resultsmentioning
confidence: 99%
“…Defects engineering in phononic crystals (PnCs) has convincingly demonstrated the feasibility of guiding waves within their acoustic bandgap when defects are optimally induced. [1][2][3] PnCs, also known as acoustic bandga+p materials, consist of sound scatterers periodically arranged in a matrix in which both components exhibit different physical properties such as mass density, speed of sound, and Young's modulus. This spatially periodic mass distribution enables the observation of acoustic or elastic bandgaps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation